Analysis of the incidence of lung cancer based on anatomical sites of lung using NIS data. (1st January 2013) - Vyas, Riddhi; Haque, Syed; Mital, Dinesh P.; Srinivasan, Shankar
Analysis concludes that the risk occurrence of lung cancer follows an order from high to low: upper lobe, lower lobe, other-parts of the lung, main bronchus, and middle lobe. We have also examined the association of each category of lung with gender and race too. The overall lung cancer analysis indicate that White and Black Americans have the higher risk of getting lung cancer as compared with other races, but anatomical category of lung cancer indicates White American are more susceptible to each category of lung except other-part of lung as compared with other races. The odds ratio analysis for each anatomical site concludes White male and female [odds ratio of all sub category – male/female 1.03 to 1.08] are equally susceptible to each category of lung. The Black females [odds ratio of lower lobe-male/female 1.08] are highly associated with lower lobe lung cancer as compared with Black males while Hispanic, Asian and Native American females are more associated with middle lobe lung cancer as compared with Hispanic, Asian and native American males [odds ratio for middle lobe – male/female 0.89 to 0.95].